Qur'an Literacy Activities for Children and Parents during Children's Study at Home - Nur Inten, Dinar; Agustina, Susanti (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose –The pandemic has forced parents and children to carry out various activities only at home. Parents who are usually busy with their office work can rebuild attachment with their children with meaningful Qur’an literacy activities. Qur’an is the life guide of every Muslim, so it is the duty of parents to introduce and set the right example to their children as early as possible. Through the direct involvement of parents and children in Qur’an literacy activities, it grows and gives birth to a generation of Quranic pride for the people. The purpose of this study was to determine the activities of children's and parents' Qur’an literacy when children have to study the Qur’an at home.Design/methods/approach –The method used in this study is a survey method with a quantitative approach. The stages include situation analysis, making a google form which was submitted to approximately 246 parents in West Java who have children in early childhood period, data processing, writing reports and conclusions.Findings –The findings of the research prove that through the ability of parents to read the Qur’an properly and correctly and the ability of parents to package Qur’an literacy activities using varied and fun methods can foster children's interest in Qur’an literacy including reading Qur’an activities, i.e., reading the Qur’an and memorize short surahs. This is evidenced by the increasing number of verses and pages that children read and the number of short Surahs these children have memorized.Research implications/limitations – The study used a survey, where the literacy activity of parents and children at home during the pandemic increased compared to before the pandemic.Practical implications –Qur’an literacy activities for children while studying at home require parents' ability to read the Qur’an, knowledge of methods, media and evaluation of good and correct Qur’an teaching. Meanwhile, the limitations in this study are the instillation of Qur’an literacy in children by parents when children study the Qur’an at home.Originality/value –Qur’an literacy activities for children by parents when children have to learn the Qur’an at home. Paper type Survey study